(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Enzyme-linked immunosorbent assay (ELISA) is an immunological assay widely used in basic science research, clinical application studies, and diagnostics. ELISA is a highly effective tool for the quantitative and qualitative determination of antigens and antibodies in biological samples. The use of this method in medical diagnostics and scientific research allows us to identify infectious diseases, establish autoimmune processes and monitor the effectiveness of therapy.